2020
DOI: 10.1111/jipb.12936
|View full text |Cite
|
Sign up to set email alerts
|

Pentatricopeptide repeat protein PHOTOSYSTEM I BIOGENESIS FACTOR2 is required for splicing of ycf3

Abstract: To gain a better understanding of the molecular mechanisms of photosystem I (PSI) biogenesis, we characterized the Arabidopsis thaliana photosystem I biogenesis factor 2 (pbf2) mutant, which lacks PSI complex. PBF2 encodes a P-class pentatricopeptide repeat (PPR) protein. In the pbf2 mutants, we observed a striking decrease in the transcript level of only one gene, the chloroplast gene ycf3, which is essential for PSI assembly. Further analysis of ycf3 transcripts showed that PBF2 is specifically required for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 70 publications
(160 reference statements)
0
26
0
Order By: Relevance
“…CFM2 promotes the splicing of the ycf3-1, trnL, ndhA, and clpP-2 introns [70]. In contrast to the aforementioned splicing factors, the PPR protein PHOTOSYSTEM I BIOGENESIS FACTOR2 (PBF2) is specifically required for ycf3-1 intron splicing, but it also cooperates with CAF1 and CAF2 [71]. With mTERF2, we have now identified a sixth factor that is involved in ycf3-1 splicing.…”
Section: Splicing Of Ycf3mentioning
confidence: 99%
See 1 more Smart Citation
“…CFM2 promotes the splicing of the ycf3-1, trnL, ndhA, and clpP-2 introns [70]. In contrast to the aforementioned splicing factors, the PPR protein PHOTOSYSTEM I BIOGENESIS FACTOR2 (PBF2) is specifically required for ycf3-1 intron splicing, but it also cooperates with CAF1 and CAF2 [71]. With mTERF2, we have now identified a sixth factor that is involved in ycf3-1 splicing.…”
Section: Splicing Of Ycf3mentioning
confidence: 99%
“…Thus, Ycf3 cooperates with the nucleus-encoded thylakoid protein Y3IP1 in the assembly of PSI in tobacco and Arabidopsis [72]. A lack of OTP51, APO1, or PBF2 consequently results in a failure to accumulate the PSI complex [65,66,71]. Moreover, otp51 and pbf2 mutant plants can only grow heterotrophically and in dim light [66,71].…”
Section: Splicing Of Ycf3mentioning
confidence: 99%
“…In plants, approximately 20 chloroplast genes (encoding proteins or structural RNAs) are interrupted by introns. RNA splicing removes the intron sequences of genes from primary transcripts to enable the production of mature mRNA with the correct genetic information [ 45 , 46 ]. RNA analyses have shown that RNA editing (mainly in the form of C-to-U base conversions) is highly widespread within the chloroplasts of land plants.…”
Section: The Characteristics Of Chloroplast Gene Expressionmentioning
confidence: 99%
“…Previous analysis of PPR proteins has demonstrated that chloroplast-localized maize PPR4 [ 62 ] and THA8 [ 63 ], and Arabidopsis OTP51 [ 64 ] and OTP70 [ 65 ], are essential for the splicing of chloroplast specific introns. Interestingly, recent studies of PPR4 [ 25 ], EMB2654 [ 66 ], PBF2 [ 67 ], and SOT5 [ 68 ] in Arabidopsis showed that these proteins play a role in the splicing of chloroplast introns through their role in the recognition of the specific RNA sequences. Arabidopsis HCF152 [ 69 ], MRL1 [ 70 ], PGR3 [ 71 ], BFA2 [ 72 ], and maize PPR5 [ 73 ] and PPR10 [ 74 ] were shown to be essential for the stabilization of chloroplast transcripts.…”
Section: Functions Of Ncmrbps In Plant Growth and Developmentmentioning
confidence: 99%